2011
DOI: 10.1136/bmj.d1110
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pain on injection of propofol: systematic review and meta-analysis

Abstract: Objective To systematically determine the most efficacious approach for preventing pain on injection of propofol. Design Systematic review and meta-analysis. Data sources PubMed, Embase, Cochrane Library, www.clinicaltrials.gov, and hand searching from the reference lists of identified papers. Study selection Randomised controlled trials comparing drug and non-drug interventions with placebo or another intervention to alleviate pain on injection of propofol in adults. Results Data were analysed from 177 random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
236
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(259 citation statements)
references
References 239 publications
(97 reference statements)
14
236
0
9
Order By: Relevance
“…The addition of lidocaine to the anaesthetic can reduce this incidence by 70−80% [13,14]. In our study, 26% of PROP patients reported pain at the injection site, despite administration of 30 mg of lidocaine (i.e., a dose higher than 0.2 mg kg -1 ).…”
Section: Discussionmentioning
confidence: 57%
“…The addition of lidocaine to the anaesthetic can reduce this incidence by 70−80% [13,14]. In our study, 26% of PROP patients reported pain at the injection site, despite administration of 30 mg of lidocaine (i.e., a dose higher than 0.2 mg kg -1 ).…”
Section: Discussionmentioning
confidence: 57%
“…1 However, propofol causes a high incidence of pain on injection, approximately 60% according to a recent review, with some patients recalling the induction of anesthesia as the most painful part of the perioperative period. 2 Various methods of reducing vascular pain caused by propofol have long been the subject of investigation. Some reports have stated that a mixed injection with lidocaine is effective.…”
mentioning
confidence: 99%
“…9 Among the various methods proposed to decrease injection pain, lidocaine pretreatment with venous occlusion is one of the most effective. 10,11 Pretreatment with 40 mg or 0.5 mg/kg lidocaine with venous occlusion of the upper limb is recommended for alleviating injection pain associated with lipid emulsion propofol administration. 10,12 Using this strategy, the overall incidence of pain on lipid emulsion propofol injection has been reported to range from 8% to 42%, while the incidence of moderate to severe pain ranges from 2% to 16%.…”
Section: Discussionmentioning
confidence: 99%